Ondansetron for pediatric concussion; a pilot study for a randomized controlled trial. Issue 5 (9th September 2016) - Gravel, Jocelyn; Carrière, Benoit; D'Angelo, Antonio; Crevier, Louis; Beauchamp, Miriam H.; Mâsse, Benoît
Abstract: Objectives: Assess the feasibility of a study evaluating one dose of oral ondansetron to decrease post-concussion symptoms at one week and one month following concussion in children aged 8 to 17 years old. Method: This was a pilot study for a randomized, triple-blind controlled trial of one dose of either ondansetron or placebo performed in a tertiary care pediatric emergency department. Participants were children aged 8 to 17 years who sustained a concussion in the previous 24 hours and visited a single emergency department. The outcome of interest was an increase from pre-concussion baseline of at least 3 symptoms from the Post-Concussion Symptom Inventory, measured at one week and at one month following concussion. The primary outcome was to determine the proportion of children who completed the assessment at one week following the intervention. Secondary outcome was the proportion of children who completed the assessment at one month following the intervention. All children, care givers, and those assessing the outcomes were blinded to the group assignment. Results: Of the 218 children presenting with a concussion during the study period, we screened 108 and found 36/108 (33%) eligible to participate and 16/108 (14.8%) agreed to participate. All enrolled patients were compliant with the intervention and follow-up. Conclusion: In our study population, approximately one-third of the screened concussion patients were eligible to participate and approximately one half of those eligible agreed to participate. Our study found that most enrolled patients preferred electronic follow-up; the noncompliance rate was minimal. Résumé: Objectifs: L'étude visait à évaluer la faisabilité d'un essai d'une seule dose d'ondansétron par voie orale afin de diminuer les symptômes postcommotionnels au bout de 1 semaine et de 1 mois après l'accident, chez des enfants âgés de 8 à 17ans. Méthode: Il s'agit d'une étude pilote préalable à un essai comparatif, à répartition aléatoire et à triple insu d'une seule dose soit d'ondansétron, soit d'un placébo, menée dans un service des urgences pédiatriques de soins tertiaires. Les participants étaient des enfants âgés de 8 à 17 ans, qui avaient subi une commotion cérébrale au cours des 24 heures précédentes et qui avaient consulté un médecin dans un seul service des urgences. Le critère d'intérêt de l'essai clinique définitif sera la persistance d'au moins 3 symptômes indiqués dans l'inventaire des symptômes postcommotionnels, au bout de 1 semaine et de 1 mois après la commotion, comparativement à la période antérieure à l'accident. Le principal critère d'évaluation de l'étude pilote consistait en la proportion d'enfants ayant rempli le questionnaire d'évaluation 1 semaine après l'intervention et le critère d'évaluation secondaire, en la proportion d'enfants ayant rempli le questionnaire d'évaluation 1 mois après l'intervention. Toutes les parties – enfants, aidants et évaluateurs des résultats – étaient tenues dans l'ignorance de la répartition des sujets dans les groupes. Résultats: Sur 218 enfants qui ont consulté pour une commotion cérébrale durant la période à l'étude, 108 ont été présélectionnés; sur ce dernier nombre, 36 (33 %) étaient admissibles à l'étude et 16 (14, 8 %) ont accepté d'y participer. Tous les sujets retenus ont observé l'intervention et respecté le suivi. Conclusion: D'après les résultats obtenus dans la population étudiée, environ un tiers des patients présélectionnés ayant subi une commotion cérébrale sont admissibles à l'étude et à peu près la moitié d'entre eux acceptent d'y participer. La plupart des sujets retenus choisissent le suivi électronique, et le taux de non-respect est minime.